Modulation of transforming growth factor β function in hepatocytes and hepatic stellate cells in rat liver injury. Issue 5 (1st May 2000) - Date, M; Matsuzaki, K; Matsushita, M; Tahashi, Y; Furukawa, F; Inoue, K
Abstract : BACKGROUND: Transforming growth factor β (TGF-β) regulates hepatocyte proliferation and biosynthesis of the extracellular matrix. AIMS: This study investigated alternations in sensitivity to TGF-β1 and binding properties for ligand in hepatocytes and hepatic stellate cells (HSC) after CCl4 administration. METHODS: Plasma TGF-β1 levels in rats after CCl4 administration were determined using ELISA. Effects of TGF-β1 were examined by DNA synthesis in hepatocytes and by measurement of fibronectin production in HSC after CCl4 administration. Binding of 125 I TGF-β1 was tested in these cells. RESULTS: Plasma TGF-β1 levels were increased as early as 24 hours and were maximal by 48 hours . The antiproliferative response to TGF-β1 decreased in hepatocytes at 48 hours and normalised at 72 hours. Fibronectin production of both normal and injured HSC was affected by TGF-β1 treatment. Cross linked ligand/receptor complexes were detected in normal hepatocytes and HSC. However, these levels decreased specifically in hepatocytes at 48 hours and normalised by 72 hours. CONCLUSIONS: Downregulation of TGF-β receptor occurred in hepatocytes after chemical insult and TGF-β1 could not transduce its antiproliferative signal. Recovery of TGF-β receptor expression causes the signal to transduce to the nucleus at 72 hours. In HSC, whenever TGF-β1 is increased, TGF-β1 can transduce its signal for fibronectin production via its receptor because signalling receptors are expressed constantly.